Chemistry and Cytotoxic Activity of Essential Oil from the Stem Bark of Calophyllum soulattri - Mah, S.H.; Ee, G.C.L.; Teh, S.S. (Asian Journal of Chemistry, 2013)
GCMS analysis of the essential oil from the stem bark of Calophyllum soulattri detected twenty components. Allo-aromadendrene was present as the most abundant component. Two other major constituents are a-gurjunene and b-eudesmene. The volatile oil exhibited moderate cytotoxicity against SNU-1, Hep G2, NCI-H23, K562, Raji, IMR-32 and SK-MEL-28 cells.